(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2021)
The present review comprises phytoconstituents and pharmacological aspects of Chenopodium album Linn. (CHENOPODIACEAE). Major class of phytoconstituents mcludes phenols, alkaloids, flavonoids, glycosides and saponins. This plant has been traditionally used as laxative, blood-purifier, antiscorbutic and anthelmintic. There, Chenopodium album holds a great potential for biological evaluation.